Graphics Creation for Television Using the Sony SMC-70G Microcomputer - Ross Mutton (The Canadian Network for Innovation in Education (CNIE), 1986)
Carleton University operates an instructional television channel across the Ottawa cable companies. There was a need to modernize the equipment used for feeding course and University activity information over the channel when not broadcasting telecourses. This article examines the selection process and describes the attributes and limitations of the microcomputer system eventually selected.